INOVASI DESA WISATA BRAYUT, KECAMATAN PANDOWOHARJO KABUPATEN SLEMAN DALAM PENINGKATAN DAYA SAING DESA WISATA - wiwitadilla_23 adilla; Muhammad Khozin (Institut Pemerintahan Dalam Negeri, 2025)
Tourism management in Brayut Tourism Village demonstrates uniqueness, namely the collective participation of the community which is able to provide equitable distribution of economic benefits while preserving local traditions. This study aims to identify and analyze the types of innovations implemented by Brayut Tourism Village in Pandowoharjo District, Sleman Regency, to increase its competitiveness as a culture-based tourism destination. The approach applied is descriptive qualitative research using data collection methods through field observations, in-depth interviews with tourism village administrators, community leaders, and analysis of relevant documents. The research findings indicate that Brayut Tourism Village has implemented a number of innovations, including diversification of tourism products based on local culture, implementation of educational tourism programs for students, utilization of digital media in promotion, and development of human resource competencies through periodic training. In addition, active community participation in managing tourism activities is an important element in the success of sustainable innovation. The findings of this study indicate that the innovations implemented in Brayut Tourism Village have significantly strengthened the village's competitiveness, as reflected in the increase in the number of visitors, increase in local revenue, and preservation of cultural sites. This achievement shows that innovation based on local resources and involving community participation is an effective way to develop a tourism village with a strong competitive advantage